Pharmacological inhibition of protein tyrosine kinases axl and fyn reduces TNF-α-induced endothelial inflammatory activation in vitro - Ellermann, Sophie F.; Jongman, Rianne M.; Luxen, Matthijs; Kuiper, Timara; Plantinga, Josee; Moser, Jill; Scheeren, Thomas W. L.; Theilmeier, Gregor; Molema, Grietje; Van Meurs, Matijs (Frontiers in Pharmacology, 2022)
Major surgery induces systemic inflammation leading to pro-inflammatory activation of endothelial cells. Endothelial inflammation is one of the drivers of postoperative organ damage, including acute kidney injury (AKI). Tumour Necrosis Factor alpha (TNF-α) is an important component of surgery-induced pro-inflammatory activation of endothelial cells. Kinases, the backbone of signalling cascades, can be targeted by pharmacological inhibition. This is a promising treatment option to interfere with aberrant endothelial inflammation. In this study, we identified activated kinases as potential therapeutic targets. These targets were pharmacologically inhibited to reduce TNF-α-induced pro-inflammatory signalling in endothelial cells. Kinome profiling using PamChip arrays identified 64 protein tyrosine kinases (PTKs) and 88 serine-threonine kinases, the activity of which was determined at various timepoints (5-240 minutes) following stimulation with 10 ng/mL TNF-α in HUVEC in vitro. The PTKs Axl and Fyn were selected based on high kinase activity profiles. Co-localisation experiments with the endothelial-specific protein CD31 showed Axl expression in endothelial cells of glomeruli and Fyn in arterioles and glomeruli of both control and TNF-α-exposed mice. Pharmacological inhibition with Axl inhibitor BMS-777607 and Fyn inhibitor PP2 significantly reduced TNF-α-induced pro-inflammatory activation of E-selectin, VCAM-1, ICAM-1, IL-6 and IL-8 at mRNA and VCAM-1, ICAM-1, and IL-6 at protein level in HUVEC in vitro. Upon pharmacological inhibition with each inhibitor, leukocyte adhesion to HUVEC was also significantly reduced, however to a minor extent. In conclusion, pre-treatment of endothelial cells with kinase inhibitors BMS-777607 and PP2 reduces TNF-α-induced endothelial inflammation in vitro.